Changing with the Times: The Evolution of Plain Language in the Legal Sphere - Williams, Christopher (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2015)
As is well known, the Plain language movement has been influential in a number of areas of public life over the last few decades. Within the legal sphere it has raised general awareness concerning the need to make legal matters and legal documents more comprehensible and accessible to non-experts, particularly in today’s digitalized world where information is freely available to the general public. In this paper my aim is to provide an overview of the way the Plain language movement has evolved in the legal sphere since the 1970s. In particular, I will highlight the following points: (1) the reasons why the Plain language movement came into being; (2) the major successes of plain language in the legal sphere over the last 40 years; (3) the areas where legalese still predominates, and the reasons for the resistance to change; and (4) the way the Plain language movement has adapted to the digitalized world and the implications for future development. My observations will be mainly restricted to the English-speaking world, including international organizations where English is one of the official languages, but I will occasionally make reference to other plain language organizations outside the English-speaking world where this seems relevant. I also provide a list of the major organizations involved in promoting plain language in English in the legal sphere today as a reference guide.